Pengaruh Variasi Fraksi Volume Terhadap Kekuatan Tarik Komposit Berpenguat Gabungan Serat Pelepah Pisang dan Serat Daun Nanas - Fajar Paundra; Zuhdi Zainul Muttaqin; Fajar Perdana Nurullah; Eko Pujiyulianto; Febri Budi Darsono (Jurusan Teknologi Produksi dan Industri, Institut Teknologi Sumatera, 2022)
Composite fiber composite is the process of making composites using 2 or more kinds of fibers as reinforcement. The choice of fiber and the volume fraction between fibers greatly affect the strength of a composite. So, it is necessary to do further research on the effect of volume fraction variations of banana midrib fiber and pineapple leaf fiber on the strength of the composite. This study aims to identify the effect of volume fraction variations of the combined banana midrib and pineapple leaf fiber on the tensile strength and flexural composites. The composite manufacturing process is carried out by the compression molding method. With variations in volume fraction of banana midrib fiber and pineapple leaf fiber, respectively 10:20, 12.5:17.5, 15:15, 17.5:12.5 and 20:10. After the molding process, the density calculation, tensile test and bending test are carried out. The results of the characterization that have been carried out show that the highest tensile strength value is in the volume fraction variation of 20:10 of 26.55 MPa and the highest value of tensile strength is obtained at the volume fraction variation of 12.5:17.5 of 66.63 MPa.